2015
DOI: 10.1016/j.bjid.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Serotype distribution and antimicrobial resistance of Streptococcus pneumoniae causing noninvasive diseases in a Children's Hospital, Shanghai

Abstract: The potential coverage of PCV13 is higher than PCV7 and PCV10 because of the emergence of 19A and there should be long-term and systematic surveillance for non-vaccine serotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…PCV13 covered more isolates in Shanghai than in other countries (Miyazaki et al, 2017; Dalcin et al, 2018), probably because it was just licensed for optional use in 2016 and had not been taken into the standard childhood immunization program in mainland China. Compared with our previous reports (Pan et al, 2015a,b), the proportion of serotype 19A and 23F decreased while 14 and 34 increased. There was a reduction of 2–5% in serotype 15B/C, replaced by the appearance of 15A, mainly from CAP.…”
Section: Discussioncontrasting
confidence: 91%
“…PCV13 covered more isolates in Shanghai than in other countries (Miyazaki et al, 2017; Dalcin et al, 2018), probably because it was just licensed for optional use in 2016 and had not been taken into the standard childhood immunization program in mainland China. Compared with our previous reports (Pan et al, 2015a,b), the proportion of serotype 19A and 23F decreased while 14 and 34 increased. There was a reduction of 2–5% in serotype 15B/C, replaced by the appearance of 15A, mainly from CAP.…”
Section: Discussioncontrasting
confidence: 91%
“…Hsueh et al [ 30 ] found 82% CA- S. pneumonia were resistant to erythromycin in Taiwan during 1996–1997. In 2012, Pan [ 31 ] et al also found high resistance to erythromycin (98.5%) in Shanghai, China. As observed by various resistance levels, high resistance rates are associated with greater exposure to antibiotics in China [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an obvious correlation between antibiotic resistance and the serotype of Streptococcus pneumoniae . For example, half of our penicillin-resistant strains have been identified as serotype 19F (Pan et al, 2015 ), therefore, the effect of vaccine introduction on antibiotic resistance cannot be ruled out. However, due to the high cost of Streptococcus pneumoniae vaccine and the low vaccination rate of children in China, the impact of vaccine use on antibiotic sensitivity of Streptococcus pneumoniae isolates remains to be evaluated (Shi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%